Serra doria procedure as an alternative treatment for end stage achalasia. A case report - Haithem Zaafouri; Mona Cherif; Nizar Khedhiri; Meriam Sabbah; Taha Sabri; Anis Ben Maamer (Heliyon, 2024)
The standard of care for achalasia is laparoscopic Heller's cardiomyotomy. This procedure achieves satisfactory and long-standing results in over 85 % of patients. However, disease progression occurs in some patients leading to end-stage achalasia, occasionally requiring oesophagectomy. In a recent systematic review and meta-analysis of 1307 patients who underwent oesophagectomy for end-stage achalasia, the pooled prevalence of pneumonia, anastomotic leakage and mortality were 10 %, 7 % and 2 %, respectively. We present a Serra Doria procedure as an alternative ‘esophagus-preserving’ procedure in a 58-year-old female patient with end-stage achalasia. This advancement highlights the crucial role of personalized care and the ongoing research necessary to enhance outcomes for those suffering from this challenging condition.